Dinosaur hunter Robert Irwin. Written by Jack Wells - Irwin, Robert 2003- (Random House Australia, 2013)
Discover a world of prehistoric dinosaur adventure with Rober Irwin! When Robert found a dinosaur fossil on a fossil dig in outback Queensland, little did he realise that he would be travelling 95 million years back in time - when dinosaurs roamed the continent of Australia. Although it was an incredible experience, would Robert be able to find his way home to the present?